2016
DOI: 10.4103/0976-7800.185336
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal uterine bleeding in perimenopausal women: Correlation with sonographic findings and histopathological examination of hysterectomy specimens

Abstract: Background:Abnormal uterine bleeding (AUB) is a frequently encountered gynecologic complaint in perimenopausal woman and also the most common cause of hysterectomy in this age group.Objective:Evaluation of various clinical presentations of perimenopausal AUB and it is ultrasonographic and histopathological correlation of hysterectomy specimens.Materials and Methods:This study was carried out in the Department of Obstetrics and Gynaecology among perimenopausal women who underwent hysterectomy for AUB. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 9 publications
(9 reference statements)
8
60
0
1
Order By: Relevance
“…According to Talukdar et al, the dominant menstrual problem in patients with abnormal uterine bleeding was menorrhagia in 44.44%. 3 In the present study, 57.5% patients had laprosterilization. The theory of increased bleeding is that delivery of hormones from the ovaries to the uterus is impaired.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…According to Talukdar et al, the dominant menstrual problem in patients with abnormal uterine bleeding was menorrhagia in 44.44%. 3 In the present study, 57.5% patients had laprosterilization. The theory of increased bleeding is that delivery of hormones from the ovaries to the uterus is impaired.…”
Section: Discussionmentioning
confidence: 87%
“…It is more common in fourth to fifth decades of life or in perimenopausal age group. 3 In present study, most of the AUB patients were in the age group of 41 to 50 years (42.50%) followed by 31 to 40 years (38.50%). N Bhavani et al observed that most of the AUB patients were in the age group of 41 to 50 years (40%) followed by 31 to 40 years (37%).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Majority of the cases of peri menopausal uterine bleeding was in age group of 45 -55 years (61 % ).In a similar study by Yogesh Neena et al , maximum cases (54.16 %) were in 45 -55 years (8) . In study by Talukdar B et al, 67.97% of patients were in in age group of 45 -55 years (9) . Thus age group of 45 -55 seems to be most vulnerable age group for uterine bleeding in peri menopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…So, perimenopausal women with heavy or irregular menstrual bleeding are often advised to have an endometrial sample taken to exclude endometrial disease. 21 Degenerative process of corpus luteum is sluggish in irregular shedding of the endometrium which leads to prolonged menstrual cycle to the waning effect of progesterone seen in 1.4% of cases. The exact cause of bleeding in atrophic endometrium is not known it is thought to be due to anatomic vascular variation or defective local haemostatic mechanism.…”
Section: 20mentioning
confidence: 99%